1983
DOI: 10.1148/radiology.146.2.6217486
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and natural history of stress fractures in U.S. Marine recruits.

Abstract: In a prospective study of stress injuries of the lower extremities of U.S. Marine recruits, we derived a frequency distribution of stress fractures. The most frequently fractured bone was the tibia (73%), while the single most common site was the posterior calcaneal tuberosity (21%). The natural history of stress fractures by scintigraphy and radiography has been outlined, showing the evolutionary changes on either study as a universal progression independent of injury site or type of stress. An identical spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
8

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(102 citation statements)
references
References 0 publications
5
89
0
8
Order By: Relevance
“…The distribution of site of stress fractures in the study was similar to other military studies [12][13][14][15], in that it showed the most affected site to be the tibia. The incidence of metatarsal fractures has been declining while the tibial incidence has been increasing [5].…”
Section: Sitesupporting
confidence: 85%
“…The distribution of site of stress fractures in the study was similar to other military studies [12][13][14][15], in that it showed the most affected site to be the tibia. The incidence of metatarsal fractures has been declining while the tibial incidence has been increasing [5].…”
Section: Sitesupporting
confidence: 85%
“…4 In a large Indian series based on similar classification by Agarwal et al it was found that the most common grade of SF was grade I. 4 However, in our series, the common grade of SF was grade II followed by grade I. Greaney et al 19 and Gracic et al 20 reported that 60% and 40% of SF, respectively, had occurred during the initial military training. According to Giladi et al the occurrence of SF was found maximum at 14 weeks of training.…”
Section: Disposal and Outcome Of All Stress Fracture Cases After Hospmentioning
confidence: 43%
“…the basic phase of training similar to the study by Giladi et al 17 The distribution of sites of SF in this study is similar to the other military studies. 19,21 The most affected bone is tibia and the common site of tibial involvement is the upper one-third which is similar to Orava et al and Singh et al 18 The lower one-third SF of tibia is common amongst recruits having mild knock knee. In our series, it was decided to study whether the intercondylar distance (relative bow leg) made any significant difference to the site of SF.…”
Section: Disposal and Outcome Of All Stress Fracture Cases After Hospmentioning
confidence: 59%
“…27 Marching in BMT appears to be an important factor that contributes to the occurrence of stress fractures. 22,26,39,40 In a study conducted on musculoskeletal injuries in officer training, Heir 41 reported that most injuries were the result of marching, infantry running and field exercises. An injury study conducted in Australian Army recruits compared a marching regimen (N ϭ 170) to a standard running regimen (N ϭ 180) and found similar injury rates, but differences in types and severity of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A number of military studies have found maximum stress fracture rates during the first 3 weeks of military training, although there is some disagreement. [22][23][24][25][26][27] On the basis of these observations, many believed that a period of rest from vigorous weight-bearing activities during the early weeks of BMT will reduce stress fractures. 28 Jones 29 proposed an approach that would allow for periods of recovery through alternating days of running and marching, so that training effects would not be diminished and risk of injury would not increase.…”
Section: Introductionmentioning
confidence: 99%